(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The subject of research is a set of theoretical and methodological provisions and applied aspects of assessing the level of the shadow economy and de-shadowing of this process. The study is based on the definition of existing methods for assessing the level of the shadow economy; clarifying the tools used in the process of assessing the shadow economy, identifying ways to de-shadow the fiscal sector and identifying tasks for the implementation of leveling this process. It is established that there are four most effective methods of estimating the size of the shadow economy: the method of "population expenditure - retail trade"; financial method; monetary method; electric method. The results of the study made it possible to propose tools for de-shadowing the fiscal market, which are to increase the level of financial literacy of the population; formation of electronic databases of violators (subjects of the shadow economy); improving the methodology for assessing the scale of the shadow economy; introduction of a tax on international speculative transactions; reforming the state’s anti-corruption policy; ensuring the principle of tax justice (equality) for taxpayers; provide an effective fiscal management of residents who use offshore jurisdictions; raising the level of legal culture of the population; legalization of shadow activity (subject to its legality); improvement of the "ProZorro" system; counteraction to financial crimes, "laundering funds"; introduction of tax amnesty and capital amnesty, etc. The purpose of the article is to substantiate the existing methods of assessing the shadow economy and to develop practical recommendations on ways and tools to de-shadow the fiscal sector. Different methods of estimating the level of the shadow economy are used at the macro- and microeconomic levels. It was found that the assessment of the shadow economy by existing methods in Ukrainian practice is not accurate, as its reliability is influenced by factors: unreliability, concealing or providing false information, the complexity of tracking "traces" of economic crimes, the scale of shadow economic activities and more. Identifying ways and measures to de-shadow the fiscal sector will reduce shadow phenomena in the domestic economy and in the fiscal sector, in particular.